Perancangan Rute Pengangkutan Sampah di Garut Dengan Model Penyelesaian Capacitated Vehicle Routing Problem (CVRP) - Chandrahadinata, Dody; Taptajani, Dedi Sa'dudin; Fathori, Moch Zain (Institut Teknologi Garut, 2025)
The problem of urban waste management is a big challenge in Garut Regency. This research designs waste transportation routes using the Capacitated Vehicle Routing Problem (CVRP) method with a combination of Saving Matrix and Nearest Neighbor algorithms. This method is more efficient than other algorithms such as genetics, with a simple application that is relevant for urban areas. The results show that the number of routes can be reduced from 12 to 9 (25%), the travel distance reduced from 518.18 km to 312.69 km (a saving of 205.49 km), and the operational cost dropped from Rp 17,618,120 to Rp 10,631,460 (a saving of Rp 6,986,660 or 39.65%). In addition to supporting cost and time efficiency, this method reduces vehicle emissions and environmental impacts. This study provides a practical solution for the Environmental Agency (DLH) and opens up opportunities for IoT technology integration in the future.